1980
DOI: 10.1149/1.2129375
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Na2 SO 4 Induced Corrosion at 600°–900°C

Abstract: The kinetics of Na2SO4-induced corrosion were measured by accelerated oxidation tests on Co-30Cr and Ni-30Cr as a function of temperature from 600~ "C, SO3 in the environment and deposit composition. The alloys were rapidly attacked at temperatures between 650 ~ and 750~C when a liquid sulfate phase was obtained from an initially pure solid Na2SO4 deposit. The rapid rate of attack resulted ~rom sulfation of the transient surface nickel or cobalt oxides and the dissolution of these transition metal sulfates int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(103 citation statements)
references
References 7 publications
4
99
0
Order By: Relevance
“…Under type II hot corrosion conditions, work by Luthra and co-workers [20,40] showed the benefit of high chromium containing alloys, with chromium contents up to 40wt%, while studies at Cranfield have demonstrated the benefits of high chromium and high aluminium levels, with an alloy containing 33wt%Cr and 33wt%Al exhibiting optimum corrosion performance at 750C [41][42][43]. Figure 3 illustrates a ternary diagram at 750C, overlayed with iso-corrosion contours [43] which demonstrates that the most corrosion resistant alloys at this temperature contain chromium levels between24-40wt% and aluminium levels between 27-37wt%, much higher than the levels in conventional MCrAlY coatings.…”
Section: Optimisation Of Corrosion Resistant Compositionsmentioning
confidence: 99%
“…Under type II hot corrosion conditions, work by Luthra and co-workers [20,40] showed the benefit of high chromium containing alloys, with chromium contents up to 40wt%, while studies at Cranfield have demonstrated the benefits of high chromium and high aluminium levels, with an alloy containing 33wt%Cr and 33wt%Al exhibiting optimum corrosion performance at 750C [41][42][43]. Figure 3 illustrates a ternary diagram at 750C, overlayed with iso-corrosion contours [43] which demonstrates that the most corrosion resistant alloys at this temperature contain chromium levels between24-40wt% and aluminium levels between 27-37wt%, much higher than the levels in conventional MCrAlY coatings.…”
Section: Optimisation Of Corrosion Resistant Compositionsmentioning
confidence: 99%
“…Under these conditions, at the base of the topcoat, temperatures may be 650 -800 8C and the bond coat could experience significant Type II corrosion attack [e.g. 1,2]. In this corrosion regime a chromia layer would be expected to offer better protection than alumina [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…From these micrographs it is evident that the CoCrAlY coating was attacked while the Pt-modified 13 and Pt+Hf-modified 7' + 7 coatings showed excellent Type II hot corrosion resistance. The poor performance of CoCrAlY coatings in Type II conditions is attributed to the formation of Na 2 SO 4 -CoSO 4 eutectic (Tmeit = 565 0 C) [49][50][51][52]. Co-based alloys and coatings are more susceptible to Type II hot corrosion attack than the Ni-based alloys and coatings because COSO 4 is more stable than…”
Section: Discussionmentioning
confidence: 99%
“…[118] [49] also showed that CoO is a better catalyst forthe SO 2 + ½ 02 -* S03 reaction than NiO and this will further increase PS 0 3 at the CoO surface than at the NiO surface.…”
Section: High Temperature Hot Corrosion (Hthc)mentioning
confidence: 99%